Migration impact on the COVID-19 pandemic in Costa Rica - Mora-Alvarado, Darner A. (2023)
The present study aims to analyse the influence or impact of foreigner’s migration on the COVID-19 pandemic evolution in Costa Rica, caused by SARS-CoV-2. The daily data of total confirmed cases of Costa Ricans and foreigners shows that the return of Nicaraguan people, from their homeland, after the period of Holy Week-04/05/2020 to 04/11/2020, has increased the number of cases in June, July and August 2020. For practical purposes, this preliminary study analyses the data ranging from 03/10/2020 to 08/01/2020. On the other hand, as the author of this study, I consider it convenient to note that it was prepared with the purpose of highlighting the importance of immigration in preventive medicine and its link with curative medicine. I would like to clarify that the intentions of writing this study were far from being xenophobic, on the contrary, I am aware of the great contribution of the Nicaraguan brothers to the Costa Rican workforce. On the other hand, it is necessary to indicate the truth to take corrective measures for the next epidemics or pandemics.